What Makes Students' Reluctance in Speaking English at Mawaridussalam Islamic Boarding School? - Husaini, M Fahri (BRIGHT VISION Journal of Language and Education, 2024)
The research conducted was entitled " WHAT MAKES STUDENTS’ RELUCTANCE IN SPEAKING ENGLISH AT MAWARIDUSSALAM ISLAMIC BOARDING SCHOOL?" which was motivated by students' reluctance in speaking English. This research uses qualitative methods. The data of this research is the result of observation, interview. Researchers collected data sources obtained from students. The data of this research are participants and sources. The main data came from in-depth interviews with students. After analyzing the data about what makes students reluctant in speaking English, there are several findings in this study, namely: shyness in speaking English, fear of being mocked by friends, and lack of understanding of English.